Augusto de Campos: 90 anos - Guerini, Andréia; Junkes, Diana; Garcia Fernandes, Frederico Augusto (Revista da Anpoll, 2021)
Apresentação do número da Revista da Anpoll em homenagem ao escritor Augusto de Campos.